Control Comparison for the Coordinate Transformation of an Asymmetric Dual Three Phase Synchronous Motor in Healthy and Single-Phase Open Fault States - Dong-Kyun Son; Soon-Ho Kwon; Dong-Ok Kim; Hee-Sue Song; Geun-Ho Lee (Energies, 2021)
The coordinate transformation method of asymmetric dual three phase synchronous motor (ADTP-SM) is a Double dq transform using two dq-axes and a vector space decomposition (VSD) model method using the orthogonality of ADTP-SM. There are several studies comparing the two methods in a healthy state, but few in a single-phase open fault state. In the healthy, when the VSD model is applied, different harmonic orders of the phase current are projected onto the dq and xy-axes (the axis for controlling harmonics of the phase current), and the two-axes are orthogonal, so it can be controlled stably. In the single-phase open fault state, the same current control logic as in the healthy situation is applied. When applying the Double dq transform, the dq-axis of the fault set fluctuates, and it affects the healthy set, so it cannot be controlled stably. When applying the VSD model, if both the dq-axis and the xy-axis are controlled, the two coordinate systems do not have orthogonality and cannot be stably controlled, due to mutual interference. However, if only the dq-axis is controlled, it can be controlled stably because there is no Cartesian coordinate system other than the dq-axis. In the healthy state and single-phase open fault state, the equation is verified through experiments and simulations, and the control stability according to the coordinate transformation is compared.